Back to the Future: Past, Present, and Future is COPD360 - Hess, Michael W. (Chronic Obstr Pulm Dis, 2016)
The treatment and management of chronic obstructive pulmonary disease (COPD) have gone through significant changes over the past decade. This plenary session, part of the 2015 COPD9USA conference, examines how the diagnosis and management of COPD has become more individualized as new phenotypes have been identified. In addition, new diagnostic and management tools are evaluated and the importance of including the patient perspective when designing a treatment plan is discussed. Finally, the future integration of technology in research, clinical communication, and disease education is introduced, including how the COPD Foundation is encouraging and facilitating these efforts. This article serves as a CME available enduring material summary of the following COPD9(USA) presentations: “The Past and Present Evidence” presenter: Stephen Rennard, MD “COPD: The Way Forward” presenter: Gerard Turino, MD “E-Cigarettes—Hope, Hype or Danger?” presenter: Russell Bowler, MD, PhD “Looking Forward” presenter Prescott Woodruff, MD “The Future is Now: A Patient Perspective” presenter: Jim Nelson “COPD360 & The Patient-Powered Research Network” presenter: John Walsh